Molecular chaperones and handling of abnormal proteins in neurodegenerative disorders - Sherman, Michael (Henry Stewart Talks, 2007)
Aggregation of proteins associated with neurodegenerative disorders, Mechanisms of aggresome formation, Suppression of the heat shock response in aging and neurodegeneration, Role of heat shock proteins in suppression of apoptosis and senescence programs
Archived at 2021/02/25